IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 112 TAHUN 2014 TENTANG PEMILIHAN KEPALA DESA DI KECAMATAN PANGKALAN LAMPAM KABUPATEN OGAN KOMERING ILIR (STUDI KASUS DESA PANGKALAN LAMPAM) - Heru Adi Putranto; Rahmawati Rahmawati (Universitas Padjadjaran, 2022)
The election of village heads based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 112 of 2014 concerning Village Head Elections includes the preparation stage for Village Head Elections, the establishment of village head elections, campaigns, and implementation n of village head elections. Election of village heads, voting, counting of votes, and determination of elected village heads. This study aims to determine the implementation of the Republic of Indonesia Minister of Home Affairs Regulation Number 112 of 2014 concerning Village Head Elections in Pangkalan Lampan District, Ogan Komering Ilir Regency. This study used a qualitative research design with descriptive methods and an inductive approach. There are 2 (two) data sources in this research, namely primary data and secondary data. Data collection techniques were carried out by means of interviews and documentation. Data analysis techniques were carried out through data reducthrough on, data display, and conclusions, on/verification. The problem with the election of the village head of Pangkalan Lampam, Pangkalan Lampam District, Ogan Komering Ilir Regency, there were problems at the preparation stage, the determination stage, and the campaign for village head candidates, as well as the village implementation stage. Head election. The committee resolved this problem by referring to the existing provisions as well as coordination and deliberation with various related parties. In the upcoming Pilkades, outreach to residents needs to be expanded so that the community can know clearly and comprehensively about their rights and obligations as members of the Pangkalan Lampam Village community in the context of the Pilkades. Invite or report to the villagers to participate in exercising their right to vote so that there will not be too many abstentions from the village head in the future.